Consumers' attitude and purchase intention towards 'green' products: a study of selected FMCGs. (15th January 2020) - Walia, Sargam Bahl; Kumar, Harish; Negi, Naveen
The present study attempts to understand the ever dynamic consumers' attitude and purchase intention towards green products under category of Fast Moving Consumer Goods. The objective of the study is to assess the consumer attitude and purchase intention towards 'green' products under key elements of marketing mix as well as identify factors that affect consumer purchase intention. A survey was carried on 500 respondents associated with four retail outlets selling green products and conventional products in Dehradun, Uttarakhand, India. Factor analysis technique was used which led to the extraction of maximum common variance from all variables. Multiple regression analysis was carried out to understand the relationship shared amongst variables. The results revealed that there is a significant effect of green marketing mix variables on the attitude towards green behaviour and purchase intention towards green products.